INFLUENCES OF THE WAVE CONDITIONS ON THE CHARACTERISTICS OF SEDIMENTS TRANSPORT AND MORPHOLOGICAL CHANGE IN THE HAI PHONG COASTAL AREA - Vinh, Vu Duy; Lan, Tran Dinh (Vietnam Journal of Marine Science and Technology, 2018)
The model system for the Hai Phong coastal area was set up based on the wave climate condition between 1992-2014 and the MORFAC (the morphological acceleration factor) method in the Delft3D model. The model results of more than 50 separate simulated scenarios show the role of each wave interval and direction on characteristics of sediment transport and morphological change in the studied area. In the case of without wave, sediments from the river settle and create deposition zone in river mouths. When the wave height increases, the erosion/deposition and sediment transport in the coastal zone increase. Due to the influence of the hydrodynamics and sediment transport, the erosion/deposition rate in the dry season is higher than that in the rainy season. The morphology strongly change in the depth less than 5 - 6 m with the rate of 20 - 50 mm/year. In the water zone of over 6 m, the morphology relatively stable and reflects an accretion trend with the rate of 10 - 20 mm/year. The simulation results also show an accretion trend in the Hai Phong coastal area. It may be a consequence of the decrease in the number of big typhoons impacted on this area in the last 20 years